Urinary Bladder Patch Made with Decellularized Vein Scaffold Seeded with Adipose-Derived Mesenchymal Stem Cells: Model in Rabbits - Piovesana, Tadeu Ravazi [UNESP]; Rodrigues, Lenize da Silva [UNESP]; Bovolato, Ana Livia de Carvalho [UNESP]; Rodríguez-Sánchez, Diego Noé [UNESP]; Rinaldi, Jaqueline Carvalho; Santos, Nilton José [UNESP]; Mori, Julia Calvi; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Birch, Lynn; Bertanha, Matheus [UNESP] (MDPI, 2022)
Background: To evaluate tissue regeneration of the urinary bladder after the implantation of a decellularized vein sown with autologous adipose-derived mesenchymal stem cells (ASC) on luminal surfaces. Methods: New Zealand rabbits (n = 10) were distributed in two groups: Group Bioscaffold alone (G1)-decellularized vena cava (1 cm2) was implanted, and Group Bioscaffold plus ACSs (G2)-decellularized vena cava (1 cm2) containing ASCs were implanted. ASCs were expanded, characterized, and maintained for one week in culture with a decellularized vein scaffold. The implants were performed under general anesthesia using a continuous suture pattern. Afterward, 21 d (day) specimens were collected and analyzed by hematoxylin and eosin (HE) histology and scanning electron microscopy (SEM). Results: The integrity of the urinary bladder was maintained in both groups. A superior regenerative process was observed in the G2 group, compared to the G1 group. We observed a greater urothelial epithelialization and maturity of the mucosa and submucosa fibroblasts. Furthermore, SEM demonstrated a notable amount of urothelial villus in the G2 group. Conclusion: Decellularized vena cava scaffolds were able to maintain the integrity of the urinary bladder in the proposed model. In addition, ASCs accelerated the regenerative process development, observed primarily by the new urothelial epithelization and the maturity of mucosa and submucosa fibroblasts.
Keywords: mesenchymal stem cell; tissue engineering; urinary bladder; urinary bladder diseases; urologic surgical procedures